My Laundry Goes Digital: Pendampingan Pemasaran Berbasis Media Sosial dan Aplikasi untuk Pemberdayaan UMKM Jasa Pencucian - Muhammad Asdian; Faizah Khaerudin; Ahmad Nashiruddin Mushoddiq Rahman; Masnawaty Sangkala; Samsinar; Hasni; Nur Zazlin; Aprin Aga; Chris Dayanti Br. Ginting S, S.E., M.Si., CTT (Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the marketing capability of My Laundry MSME through the implementation of digital marketing strategies. The main problem faced is the limited use of digital media and the lack of optimal promotional strategies, resulting in low market reach. The method used is a participatory approach consisting of observation, socialization, training, and evaluation stages. The training focused on understanding digital marketing concepts and hands-on practice in creating and managing social media platforms, particularly Instagram and TikTok. The results show that the MSME now has more professional and structured social media accounts, actively produces promotional content, and utilizes Linktree to facilitate customer access to services. The implementation has increased business visibility, as indicated by reach, profile visits, and user engagement metrics. Thus, digital marketing has proven to have a positive impact in supporting promotion and business development of My Laundry MSME, although consistency in content management and continuous evaluation are still needed to achieve optimal and sustainable results.